PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI ASAM BASA DI KELAS XI IPA SMA ADVENT MANOKWARI - Sari, Novi Dian; Fahzal, Nur Arifah Adila; Faisal, Faisal (Arfak Chem: Chemistry Education Journal, 2023)
This study aims to determine the influence and differences in cognitive learning outcomes among students using the NHT-type cooperative learning model. This research uses a pre-experimental design in the form of a one-group pretest-posttest design. The sampling technique involves gathering data through observation, interviews, posttests, and documentation. The results obtained were a mean pretest score of 42.09 and a posttest mean of 74.96. The hypothesis test yielded a t-test with a Sig value (2-tailed) of 0.000, indicating a significant impact on the cognitive learning outcomes of students taught using the NHT type cooperative learning model, with a 78% influence. The N-Gain analysis, with a value of 0.61, classifies the students' understanding of the acid-base material with NHT as moderate.